Beyond the Golden Era of public health: charting a path from sanitarianism to ecological public health. Issue 10 (October 2015) - Lang, Tim; Rayner, Geof
Abstract: The paper considers the long-term trajectory of public health and whether a 'Golden Era' in Public Health might be coming to an end. While successful elements of the 20th century policy approach need still to be applied in the developing world, two significant flaws are now apparent within its core thinking. It assumes that continuing economic growth will generate sufficient wealth to pay for the public health infrastructure and improvement needed in the 21st century when, in reality, externalised costs are spiralling. Secondly, there is evidence of growing mismatch between ecosystems and human progress. While 20th century development has undeniably improved public health, it has also undermined the capacity to maintain life on a sustainable basis and has generated other more negative health consequences. For these and other reasons a rethink about the role, purpose and direction of public health is needed. While health has to be at the heart of any viable notion of progress the dominant policy path offers new versions of the 'health follows wealth' position. The paper posits ecological public health as a radical project to reshape the conditions of existence. Both of these broad paths require different functions and purposes from their institutions, professions and politicians. The paper suggests that eco-systems pressures, including climate change, are already adding to pressure for a change of course.